2000
DOI: 10.1128/jvi.74.10.4530-4540.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of a Novel Heparin-Binding Glycoprotein Encoded by Human Herpesvirus 7

Abstract: Human herpesvirus 6 (HHV-6) and HHV-7 are closely related betaherpesviruses that encode a number of genes with no known counterparts in other herpesviruses. The product of one such gene is the HHV-6 glycoprotein gp82-105, which is a major virion component and a target for neutralizing antibodies. A 1.7-kb cDNA clone from HHV-7 was identified which contains a large open reading frame capable of encoding a predicted primary translational product of 468 amino acids (54 kDa) with 13 cysteine residues and 9 potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In that study, gp65 was detected in HHV-7 virions and interacted with heparin and heparan sulfate proteoglycans, and gp65-specific antiserum neutralized the infectivity of virus inocula (33). These findings suggested that HHV-7 gp65 may contribute to the attachment of the virus to cell surface proteoglycans (33).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In that study, gp65 was detected in HHV-7 virions and interacted with heparin and heparan sulfate proteoglycans, and gp65-specific antiserum neutralized the infectivity of virus inocula (33). These findings suggested that HHV-7 gp65 may contribute to the attachment of the virus to cell surface proteoglycans (33).…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, gQ positional homologs have also been reported in human HHV-7, as HHV-7 gp65 (33). In that study, gp65 was detected in HHV-7 virions and interacted with heparin and heparan sulfate proteoglycans, and gp65-specific antiserum neutralized the infectivity of virus inocula (33).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The It has been shown, however, that two HHV-7 glycoproteins, gB and a novel glycoprotein called gp65, can bind to heparin and heparan sulfate (22,23). By analogy with other herpesviruses, it seems likely that binding of these glycoproteins to heparan sulfate has a role in the binding of virus to cells.…”
mentioning
confidence: 99%
“…Although the overall picture is still far from being complete, it has become clear during the past few years that viruses from many different families interact with GAGs, in most cases heparan sulfate (HS) (7,8,11,12,14,15,18,20,34,35,38,40,50,59,61,62,63,67,70), and it has been proposed that the affinity of the viral surface for HS may be an important determinant of tissue tropism and pathogenicity (5,9,17,30,48,65). In most cases the affinity of the virus for HS seems to be relatively low and may serve the purpose of concentrating the virus on the cell surface to facilitate subsequent binding to one or more high-affinity receptors (6,21,33,53,58).…”
mentioning
confidence: 99%